Study of acute and chronic toxicity of homeopathic syrup Stodal - S. V. Alekseeva; A. V. Sorokina; V. V. Zabrodina; I. A. Miroshkina; A. S. Lapitskaya (LLC "Publisher OKI", 2020)
The study of acute and chronic toxicity of the homeopathic preparation syrup Stodal, produced by the Laboratory of Boiron, France, widely used in medical practice as an effective antitussive agent. Stodal with a single intragastric administration to outbred mice and rats at doses of 5, 10, 15, 20 and 25 ml / kg and intraperitoneal administration to rats at doses of 2.5; 5; 7.5; 10 and 12.5 ml / kg did not cause death of animals. In experiments on mice in females with intraperitoneal administration of homeopathic syrup Stodal LD50 was 17.2 (13.1 - 22.6) ml/kg and in males LD50 was 19.6 (16.1 - 24.0) ml/kg. Homeopathic syrup Stodal with daily oral administration to rats and rabbits in doses of 1 ml / kg and 10 ml/kg for one month did not cause changes in the General condition, behavior, appearance and pronounced changes in body weight of animals. Toxic effects of stodal syrup were not observed in clinical and laboratory, pathomorphological and histological studies performed in the conventional volume.